2012
DOI: 10.1016/j.neuron.2012.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Mechanisms Support the Voluntary Forgetting of Unwanted Memories

Abstract: SummaryReminders of the past can trigger the recollection of events that one would rather forget. Here, using fMRI, we demonstrate two distinct neural mechanisms that foster the intentional forgetting of such unwanted memories. Both mechanisms impair long-term retention by limiting momentary awareness of the memories, yet they operate in opposite ways. One mechanism, direct suppression, disengages episodic retrieval through the systemic inhibition of hippocampal processing that originates from right dorsolater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
449
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 314 publications
(497 citation statements)
references
References 50 publications
42
449
6
Order By: Relevance
“…2015). Another study revealed differences among strategies used to suppress unwanted thought and confirmed that direct suppression involves a part of the right frontoparietal network (FPN) (Benoit and Anderson 2012). The relevance of the right LPFC in the inhibitory process has also been noted by a body of clinical studies on OCD as well as attention‐deficit hyperactivity disorder (Depue et al.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…2015). Another study revealed differences among strategies used to suppress unwanted thought and confirmed that direct suppression involves a part of the right frontoparietal network (FPN) (Benoit and Anderson 2012). The relevance of the right LPFC in the inhibitory process has also been noted by a body of clinical studies on OCD as well as attention‐deficit hyperactivity disorder (Depue et al.…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, one possible interpretation of the major SMG recruitment observed in our findings would be that thought suppression involves the suspension of thinking. Because we instructed the participants to simply clear their minds as much as possible without specifying the subject to suppress, the participants must have employed direct suppression instead of substitution (Benoit and Anderson 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Following on recent work, we examined whether the content of suppressed memories would become less visible to observers on a later visual perception test (20). To detect difficulties in perception, we adapted the "think/ no-think" procedure developed to study how people suppress unwanted memories (1)(2)(3)(4)(5)(6)20) (Fig. 1A).…”
Section: Significancementioning
confidence: 99%
“…On each trial, participants received the cue from one of the pairs (e.g., "duty"), and were asked either to recall its paired object (e.g., "binoculars;" think trials), or instead to prevent the object from entering conscious awareness (nothink trials). For no-think trials, we asked participants not to generate distracting thoughts, but to focus on the reminder, and to suppress the object from awareness if it intruded (5).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation